Superior Leadership and its Impact on Superior Performance Through Inspiration in the Workplace: An Applied Study at Al-Kafeel Private University - Alabedi, Ali; Hussein, Kais; Al-Haboobi, Mohammed (The Arab Journal of Administration, 2021)
Today business organizations seek to free up all the potentials of individuals working to achieve high performance. Recent literature has unveiled that this goal is difficult to achieve unless there is unconventional leadership capable of inspiring workers inside organization, workplace inspiration has a vital role in empowering workers in bypassing challenges and obstacles in order to achieve superior performance, The present study aimed to investigate the role of superior leadership in enhancing the superior performance through the intermediate effect of workplace inspiration. The study adopted a quantitative approach based on the questionnaire which Was distributed to the employees of the University of the sponsor (105) employees, has been retrieved (88) questionnaire valid for statistical analysis. Using PLS-SEM modeling, there was a significant direct effect for superior leadership on both workplace inspiration and superior performance. In addition, there is a significant indirect effect (mediation) indirect effect for super leadership on superior performance through the intermediate effect of workplace inspiration. The study concluded the importance of developing super leadership practices and providing a culture that fosters inspiration in the workplace to reflect positively on super performance.